Study of Prevalence of Preoperative Corneal Astigmatism in Patients with Senile Cataract at a Tertiary Care Institute in South India - C. Kumar Amruth; P. Ramya Deepthi; K. Sushma (Journal of Ophthalmology, 2022)
Background. The prevalence of corneal astigmatism in patients with cataract has not been well documented in both rural and urban areas of Indian population.